Comparing the effectiveness of acceptance and commitment therapy(ACT) and paradoxical time table therapy (PTC) on the psychological well-being of nurses - Leila Taghilo; Leila Sadat Azizi Ziabari; Afsaneh Khajevand Khoshli; Masomeh Damghani Mirmahaleh (فصلنامه ابن سینا)
Background and aims: Recently, new solutions have been presented to increase the well-being of people in different jobs, the extent of their effectiveness is unknown; so the present study was conducted with the aim of comparing the effectiveness of acceptance and commitment therapy (ACT) and paradoxical time table therapy (PTC) on the psychological well-being of nurses Methods: This was a semi-experimental study with pre- and post- tests and control group. The statistical population of the present study was made up of all 125 nurses who met the criteria for entering the study working in different departments of Military medical centers in 2023. Totally, 45 nurses working in different wards of a military medical center in 2022 were selected as available sample and were randomly assigned to three groups of 15 people (two experimental groups and one control group). ACT group participated in eight individual- 60-minute sessions and PTC group participated in six individual 60-minute sessions; but there was no intervention for the control group. The short form of Ryff psychological well-being questionnaire was used. To analyze the data, multivariate covariance analysis and Tukey's post-hoc tests were used. Results: The findings showed that ACT and PCT have an effect on the psychological well-being of nurses (p≤0.01). But ACT is more effective than PTC on psychological well-being (p≤0.01). Conclusion: This research provided practical findings for mental health professionals regarding the greater effect of ACT on psychological well-being.